Performance analysis of grooved hydrodynamic journal bearing with multi- depth textured surface - Faez, K.M. (MechAero Found. for Techn. Res. and Educ. Excellence, 2018)
In recent research, theoretical studies and investigations for the textured surface of a hydrodynamic journal bearing has been widely used. This is due to the journal bearing's performance in terms of load capacity which affects the system performance, efficiency and reliability. It has been proven that a textured surface and grooved surface have managed to improve the performance of journal bearings to some extent. In this work, the performance of a grooved hydrodynamic journal bearing has been analysed with a multi-depth textured surface. The study has been conducted using the modified Reynolds equation to numerically solve the load capacity and pressure distribution, respectively. From the results obtained, it was found that the surface complexity features on the journal bearing lowered the load capacity performance when compared to the plain bearing. The pressure, meanwhile, was distributed throughout the textured sections on the bearing surface, even though it was lower as compared to the plain bearing. Â© 2018.